2018
DOI: 10.1111/jmi.12702
|View full text |Cite
|
Sign up to set email alerts
|

Application of a reflective microscope objective for multiphoton microscopy

Abstract: Reflective objectives (ROs) mitigate chromatic aberration across a broad wavelength range. Yet, a systematic performance characterisation of ROs has not been done. In this paper, we compare the performance of a 0.5 numerical-aperture (NA) reflective objective (RO) with a 0.55 NA standard glass objective (SO), using two-photon fluorescence (TPF) and second-harmonic generation (SHG). For experiments spanning ∼1 octave in the visible and NIR wavelengths, the SO leads to defocusing errors of 25-40% for TPF images … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…To further improve image quality, it is possible to combine the Schmidt objective with adaptive optics. Owing to their low dispersion and large wavelength range, reflective objectives have previously been used for multi-photon microscopy 23 , 24 but not as fully immersed systems. We think that our work opens an unexplored design space for building immersion microscope objectives.…”
Section: Discussionmentioning
confidence: 99%
“…To further improve image quality, it is possible to combine the Schmidt objective with adaptive optics. Owing to their low dispersion and large wavelength range, reflective objectives have previously been used for multi-photon microscopy 23 , 24 but not as fully immersed systems. We think that our work opens an unexplored design space for building immersion microscope objectives.…”
Section: Discussionmentioning
confidence: 99%
“…Obscuration refers to mechanical light attenuation from mirror design, where a significant portion of light entering the objective fails to reflect to a secondary mirror, and an additional fraction is obstructed by thin suspensions used to mount the primary mirror. Encouragingly, simulation has shown that back-reflections may be minimized by the adoption of annular-shaped beams in favor of Gaussian profiles [13]. Moreover, reflective objectives' transmission properties (>99% from 450 nm to 20 μm) vastly outperform traditional refractive objectives with NIR coatings, including optimized multiphoton objectives (~70% from 1100 to 1400 nm) [14].…”
mentioning
confidence: 99%